(untitled) (Proceedings of the International Conference on Future of Women, 2025)
The susceptibility to the effects of climate change is intensified by the disparity and exclusion associated with geographical location, ethnic background, gender, poverty, and other economic and social determinants. This qualitative study investigated the living conditions of the urban poor in informal settlements of Hopley, Zimbabwe and illustrate how the appropriation of private, parochial, and public spaces by female residents of Hopley informal settlement affects their ability to manage climatic risks. Informal settlements are characterized by substandard dwellings or shanties constructed in violation of formal laws and regulations. The informal community of Hopley do not have access to clean potable water or sufficient infrastructure for public health, drainage, and essential services. This paper examined strategies for developing resistance to the impacts of climate change by women in informal communities such as Hopley. The research offers valuable insights on the varying degrees of women’s participation in climate resilience development, based on a comprehensive analysis of existing literature and in depth interviews of 12 women living in Hopley. It additionally examined the measures being taken to tackle climate resilience in informal settlements, specifically, initiatives sponsored by the local community to improve settlements and strengthen their capacity to endure the effects of climate change and support marginalized populations. Furthermore, the study explored strategies for overcoming obstacles to achieving larger scale and effectiveness, such as using synergies with the Sustainable Development Goals.